1989
DOI: 10.1093/brain/112.6.1587
|View full text |Cite
|
Sign up to set email alerts
|

The Origins of Utilization Behaviour

Abstract: Utilization behaviour has previously been described clinically by Lhermitte (1983). An experimental investigation is reported of utilization behaviour in a patient with a localized inferior medial bifrontal lesion. The patient picked up and used irrelevant objects not only when place directly in front of him--the procedure developed by Lhermitte--but also when he had been instructed to carry out other tasks and his attention had not been directed to the objects. The behaviour occurred most frequently in the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
151
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 288 publications
(161 citation statements)
references
References 0 publications
6
151
0
4
Order By: Relevance
“…Lhermitte's patients considered every object falling in their visual field as a potential target for a possible action (utilization behavior) or were compelled to replicate movements executed in front of them without any evident necessity to do it (imitation behavior). Years later, other authors confirmed these observations (Cambier, 1999;Shallice, Burgess, Schon, & Baxter, 1989). However, despite the growing number of new anatomical and neurophysiological evidences on the PFC functions, the mechanism responsible of such behavior has not been yet understood.…”
Section: Introductionmentioning
confidence: 90%
“…Lhermitte's patients considered every object falling in their visual field as a potential target for a possible action (utilization behavior) or were compelled to replicate movements executed in front of them without any evident necessity to do it (imitation behavior). Years later, other authors confirmed these observations (Cambier, 1999;Shallice, Burgess, Schon, & Baxter, 1989). However, despite the growing number of new anatomical and neurophysiological evidences on the PFC functions, the mechanism responsible of such behavior has not been yet understood.…”
Section: Introductionmentioning
confidence: 90%
“…The core characteristics of utilization behavior as they arise from the literature seem to be the following. The patients needlessly, 'without any internal motivation' (Lhermitte, 1983, p. 253), and often inappropriately grasp and use objects when they see them, even when explicitly told not to do so (Lhermitte, 1983;Shallice et al, 1989). Moreover, they are not concerned or distressed about the fact that they are acting inappropriately Lhermitte, 1983Eslinger, 2002;Boccardi et al, 2002).…”
Section: Characteristics Of Utilization Behaviormentioning
confidence: 99%
“…In this sense, the ACC may be considered as a key area in the tuning of earlier stages of task-driven allocation of attention prior to stimulus processing [Gitelman et al, 1999;Woldorf et al, 2001]. It can be maintained that the ACC plays a function quite similar to that of a ''supervisory attentional system'' [Shallice, 1988;Shallice et al, 1989], which would manage repetitive stimulation in routine conditions and would alert the dorsolateral PFC when the environment unexpectedly changes and proper cognitive processes and reactions have to be set [Luks et al, 2002;MacDonald et al, 2000].…”
Section: Introductionmentioning
confidence: 99%